Spectators' Violence at Soccer Matches: A Complex Psycho-Social Phenomenon - Maksum, Ali (Faculty of Psychology, Universitas Surabaya, 2010)
The aim of this research was to understand the root cause of the Soccer supporters’ violence as well as to explore its pattern. A case study was taken from the Persebaya supporters, which are well known as “Bonek.” This research was conducted using the integrative method of quantitave and qualitative design. The result indicated that the supporter’s violent behavior isn’t caused by one aspect only, but it is a multifaceted psychosocial problem, which includes an over-fanaticism, a lack of emotional control, a disappointing management of the soccer match, and a low socioeconomic status. If the main factors such as poverty, unemployment, the management of soccer match, and the emotional behavior control aren’t improved, then the next outbreak of supporters’ violence is only a matter of time and intensity. Penelitian ini bertujuan untuk memahami akar kekerasan suporter Sepakbola dan menemukan pola tindak kekerasan yang dilakukan. Sebagai studi kasus diambil suporter Persebaya Surabaya yang lebih dikenal dengan sebutan Bonek. Penelitian dilakukan dengan metode kuantitatif dan kualitatif secara terintegrasi. Hasil penelitian menunjukkan bahwa fenomena kekerasan suporter bukanlah beralur tunggal, tetapi bersifat multidimensi yang mencakup variabel psiko-sosial seperti fanatisme berlebihan, emosi individu, penyelenggaraan pertandingan yang mengecewakan, dan kondisi sosial- ekonomi. Bila kondisi dasar seperti kemiskinan dan pengangguran tidak diperbaiki, demikian juga manajemen penyelenggaraan pertandingan dan pengendalian emosi individu, maka pecahnya kekerasan suporter kembali hanya soal waktu dan intensitas.